Establishment of best practice for means of escape in green building-adapted hospital / Adnin Syaza Jaafar - Jaafar, Adnin Syaza (2018)
Hospital can be described as a complex concept of building. The safe evacuation to the occupants in case of fire to place of assembly is essential. However, excessive design of green elements adaptation in hospital building could lead to difficulty during evacuation. This research aim to establish the best practice of Means of Escape for green building-adapted hospital. There are three objectives of this research. First, to identify the fulfilment of the design criteria of Means of Escape required by Uniform Building By-Law and other building regulations in hospital building. Second, to determine the functionability of the building design towards the existence Means of Escape in hospital building. Third, to evaluate the effects of the integration between green elements and fire safety towards Means of Escape in hospital building. A comprehensive literatures review on the design criteria of means of escape, green elements and its effect towards fire safety in hospital building are carried out.